Fabrication, stability and rheological properties of zein/chitosan particles stabilized Pickering emulsions with antioxidant activities of the encapsulated vit-D3 - Shah, Bakht Ramin; Xu, Wei; Mráz, Jan (International journal of biological macromolecules, 2021)
Pickering emulsions have been known to be promising candidates for encapsulating and delivering a wide range of bioactive compounds with antioxidant potentials. In this work, we formulated and characterized zein (ZN)/chitosan (CS) stabilized Pickering emulsion. The prepared emulsions were firstly characterized by droplet size after preparation and after storage for one month at room temperature as well as after the addition of prebiotic gum Arabic (GA). Rheological measurements were further carried out to see the behavior and stability of these emulsions after storage. Thereafter, vit-D3 was encapsulated, and the antioxidant activity of the emulsions system were evaluated. The results showed that no significant change in the mean droplet diameter of the emulsions was observed after storage for a month. This claim was further confirmed by their rheological measurements particularly, the emulsions prepared with ZN/CS ratio of 1:2 having 50% oil contents exhibited significant stability. GA addition caused a gradual increase in the droplet size up to some level, after which it led to complete destabilization of the emulsion. Finally, to protect and deliver, vit-D3 was successfully loaded in these emulsions. No significant difference in the DPPH radical scavenging activity of the vit-D3 encapsulated emulsions was observed, showing their capability as delivery vehicles irrespective of their composition.
Keywords: emulze; Gum Arabic; antioxidancia; Nanocapsules; Vitamins; Pickering emulsion; Antioxidants; vitaminy; Emulsions; Chitosan; Cholecalciferol; arabská guma; Zein; chitosan; Rheology; Characterization; zein; reologie; Vit-D(3) loading; cholekalciferol; nanokapsle; Antioxidant activity